A Identifikasi Bakteri Patogen Pada Ikan Nyalian (Rasbora lateristriata) Yang Didomestikasi - I Gede Arya Sukman Jaya; Sang Ayu Made Putri Suryani; Ni Made Darmadi; I Wayan Arya (Fakultas Pertanian, Universitas Warmadewa, 2023)
This study aims to identify pathogenic bacteria in domesticated Rasbora lateristriata fish. Sampling was carried out 1 time with the point of collection in the upstream, middle and downstream parts of the Medium river, District. Abiansemal, Badung Regency. Sampling was carried out in March 2022, using nets and nets. The data processing method is descriptive and data presentation is in the form of graphs. The domestication method aims to identify bacteria that attack Rasbora, Sp, and survive domestication. Sample examination was carried out at the Domestic Laboratory at the Denpasar Veterinary Center once. The results showed that the Nyalian Fish (Rasbora Lateristriata) which was domesticated from 5 samples found that Proteus sp. In addition, the water quality in the original habitat of Rasbora lateristriata fish with the water quality where it is adapted is different, especially the temperature, pH and DO values, but the water quality is still within the tolerance of Rasbora lateristriata fish to live.